2014
DOI: 10.1183/09031936.00024314
|View full text |Cite
|
Sign up to set email alerts
|

Prospective validation of the endurance shuttle walking test in the context of bronchodilation in COPD

Abstract: This study focused on repeatability data and minimal important difference (MID) estimates of the endurance shuttle walking test (ESWT).255 chronic obstructive pulmonary disease patients (forced expiratory volume in 1 s 54.7¡13.2% predicted) completed four ESWTs at different times during the 8-week study: two under baseline conditions with tiotropium (1 week apart), one after a single dose and one after 4 weeks of either fluticasone propionate/salmeterol combination or placebo in addition to tiotropium. 97 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 40 publications
1
23
0
1
Order By: Relevance
“…These ESWT changes represented 13-15% of baseline values. These figures were confirmed by the same authors in a multicentre trial including 255 patients in which changes of 56-61 s and 70-82 m in ESWT were perceived by the participants as relevant [194] (table 2).…”
Section: Clinical Meaningful Differencesupporting
confidence: 72%
See 2 more Smart Citations
“…These ESWT changes represented 13-15% of baseline values. These figures were confirmed by the same authors in a multicentre trial including 255 patients in which changes of 56-61 s and 70-82 m in ESWT were perceived by the participants as relevant [194] (table 2).…”
Section: Clinical Meaningful Differencesupporting
confidence: 72%
“…Thus, coefficient of variations have been reported to range between 60% and 120% of the corresponding means [174,[194][195][196][197][198]. While no recommendation on how to adjust test duration has yet been proposed, it is reasonable to assume that the range of baseline test durations used for the CWRET is desirable (i.e.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a separate study, E ngelkes et al . [25] found that LABA monotherapy was decreasing but, despite the guidelines, the prevalence remains at 1.44 per 100 per year. Although few studies have addressed clinical effectiveness in childhood asthma, research of this kind gives a major insight into the problem and may be complimentary to the results reported in randomised controlled trials.…”
Section: Paediatric Asthma and Allergymentioning
confidence: 99%
“…En nuestro estudio, tanto la distancia como el tiempo alcanzados en el EST se duplicaron en relación al valor basal y superaron ampliamente la MCID (277,281). Estos resultados significan que los cambios obtenidos fueron percibidos como una mejoría clínica por los pacientes.…”
Section: Efectos a Corto Plazounclassified